5. Edukacja i polityka edukacyjna współczesnego Kirgistanu .......... 245 (Kirgistan – oblicza transformacji, 2020)
EDUCATION AND EDUCATIONAL POLICY IN MODERN KYRGYZSTANKyrgyzstan took over the Soviet-organized educational system after 1991. Since the beginning of independence, the Kyrgyz authorities have been implementing an inconsistent program of adapting the teaching organization in the republic to European standards, while struggling with the lack of financial resources, the problem of the demographic explosion and the resulting excessive increase in the number of students and a decline in teacher authority. The chapter focuses on changes taking place both in primary and secondary education and in higher education in the republic.